Association between low-density lipoprotein cholesterol and sudden cardiac arrest in people with diabetes mellitus - Kim, Yun Gi; Jeong, Joo Hee; Han, Kyung-Do; Roh, Seung-Young; Min, Kyongjin; Lee, Hyoung Seok; Choi, Yun Young; Shim, Jaemin; Choi, Jong-Il; Kim, Young-Hoon (Cardiovascular diabetology, 2023)
Background Dyslipidemia measured as low-density lipoprotein (LDL)-cholesterol is an established risk factor of cardiovascular disease, which is more pronounced in diabetes population. Less is known about the association of LDL-cholesterol level and sudden cardiac arrest (SCA) risk in diabetes mellitus patients. This study investigated the association of LDL-cholesterol level and SCA risk in diabetes population. Methods This study was based on Korean National Health Insurance Service database. Patients who received general examination from 2009 to 2012 and diagnosed as type 2 diabetes mellitus were analyzed. Primary outcome was defined as SCA event identified with International Classification of Disease code. Results A total of 2,602,577 patients were included, with total follow-up duration of 17,851,797 person * year. Mean follow-up duration was 6.86 years, and 26,341 SCA cases were identified. Overall incidence of SCA was highest in the lowest LDL-cholesterol group (< 70 mg/dL) and decreased in a linear manner as LDL-cholesterol rises, till 160 mg/dL. Adjustment of covariates resulted in U-shape association, with highest risk of SCA in the highest LDL-cholesterol group (≥ 160 mg/dL) followed by lowest LDL-cholesterol group (< 70 mg/dL). In subgroup analysis, U-shape association between SCA risk and LDL-cholesterol was more pronounced in male, non-obese people, and those who did not use statins. Conclusions In people with diabetes, the association between SCA and LDL-cholesterol level was U-shaped with highest and lowest LDL-cholesterol group having higher risk of SCA than others. Low LDL-cholesterol level can be a surrogate marker for increased risk of SCA in people with diabetes mellitus and this paradoxical association should be recognized and extended to clinical preventive measures.